Conjugalidade lésbica na terceira idade: perspectivas apresentadas sob o olhar da literatura e das narrativas pessoais - Meloni, Lia Maraucci (2022)
This dissertation seeks, from the exposition of two complementary articles, to delve deeper into the intersection drawn between old age and lesbian relationships, which are portrayed from the perspective of scientific literature and also from the personal view of elderly lesbian women. Thus, this text is organized into two large segments, starting with the presentation of the first article, which consists of a systematic review of the literature covering older lesbian women and how their conjugalities have been represented, followed by the presentation of the second article, which consists on the thematic analysis of narrative interviews, seeking to reflect on marital relationships and aging in lesbian elders from their own perspectives. Considering that it is a subject that is sometimes invisible, bringing the lesbian experience to the center of discussions, deepening and producing perspectives about their conjugalities and aging, becomes an exercise of great importance, since these are aspects that directly influence in their life quality. Besides, to contribute with the visibility of elderly women is also a way to affirm their existence and resistance in the face of oppressive contexts.